Pengaruh Formula Bionematisida Bakteri Endofit Bacillus sp. terhadap Infeksi Nematoda Meloidogyne sp. pada Tanaman Kopi - Rita Harni; Samsudin Samsudin (Jurnal Tanaman Industri dan Penyegar, 2015)
Meloidogyne sp. is an important pathogen of coffee plant.  Bacillus sp. is commonly used to control the nematode as it is environmentally friendly. The study aimed to determine the effect of endophytic bacteria Bacillus sp. PG76 formulated in the molasses, talc or compost on the infection of Meloidogyne sp. The experiments were conducted in the laboratory and greenhouse of the Indonesian Industrial and Beverage Crops Research Institute, Sukabumi from December 2013 to May 2014. The experimental design was a completely randomized, 6 treatments and 10 replications of six months-old coffee plants. Six treatments were tested (Bacillus sp. PG76 formulated in molasses, compost, or talc; carbofuran; plant inoculated with the nematode only, and plant neither treated with the formula nor the nematode).  Population of Bacillus sp. PG76 in each formula was 109 cfu/ml. Number of formulas applied per plant was 100 ml of molasses, 100 g of talc, or 100 g of compost.  One week after the treatments, the plants were inoculated with 500 larvae-2 Meloidogyne sp. Parameters observed were the number of gall, nematode population in the roots and soil, and the coffee plant growth.  The results showed that all the treatments (molasses, compost, and talc) suppressed the population of Meloidogyne sp.  The best formulas were molasses and compost that reduced the nematode infection up to 74.0% and 73.2%, respectively, similar to that of carbofuran (i.e. 73.3%). Furthermore, application of the formulas increased coffee plant growth. The study suggests that Bacillus sp. PG76 formulation is prospective to control the nematode.